2014
DOI: 10.1111/are.12590
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization ofp38gene in the Chinese Mitten Crab,Eriocheir sinensis

Abstract: p38 is an important component of the MAPK signaling pathways as a Ser/Thr protein kinase. We cloned the full length p38 (Es-p38) cDNA sequence in Eriocheir Sinensis which contained a 1098nucleotide ORF that encoded a protein of 365 amino acids. Es-p38 protein has a p38 MAPK functional domain (STKc_p38), it is a typical serine/threonine kinase and processes all p38 protein's conservative T-G-Y motif. Tissue expression of the Es-p38 gene and expression during testis development stages were determined by quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“… found that p38 is highly expressed in the muscle of Branchiostoma belcheri . Similarly, in Eriocheir sinensis and Litopenaeus vannamei , muscle is also the tissue with highest expression rate of p38 . Our results showed that Hm‐p38a expresses in all examined tissues, but muscle shows the highest relative expression rate.…”
Section: Discussionsupporting
confidence: 53%
“… found that p38 is highly expressed in the muscle of Branchiostoma belcheri . Similarly, in Eriocheir sinensis and Litopenaeus vannamei , muscle is also the tissue with highest expression rate of p38 . Our results showed that Hm‐p38a expresses in all examined tissues, but muscle shows the highest relative expression rate.…”
Section: Discussionsupporting
confidence: 53%
“…Diluted synthesized cDNA was used as a template. This analysis was conducted on the CFX96™ Real‐Time System (Bio‐Rad), using two pair gene‐specific primers (Per1‐Q‐F, Per1‐Q‐R, Per2‐Q‐F, Per2‐Q‐R; Table ), with β‐actin (GenBank accession number: KY356885.1) as an internal control gene (Zhao, Guo, et al, ; Zhao, Wang, et al, ). Studies have shown that β‐actin is one of the most reliable reference genes and had been used widely in E. sinensis after its stability being verified (Fang et al, ; Huang et al, ; Li et al, ; Liu, Wang, et al, ; Mu et al, ; Xu et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Table 1), with β-actin (GenBank accession number: KY356885.1) as an internal control gene (Zhao, Guo, et al, 2016;Zhao, Wang, et al, 2016). Studies have shown that β-actin is one of the most reliable reference genes and had been used widely in E. sinensis after its stability being verified (Fang et al, 2016;Huang et al, 2015;Li et al, 2008;Mu et al, 2009;Xu et al, 2016).…”
Section: Tissue Distribution Analysismentioning
confidence: 99%
“…In a separate study, we were able to successfully clone the full-length p38 cDNA sequence of the Chinese mitten crab Eriocheir sinensis (GenBank accession no. KF582665) and confirmed it to be a homologue of p38α (MAPK14) by sequence alignment (Zhao et al, 2014).…”
Section: Introductionmentioning
confidence: 76%